Modelling, simulation and control of the dyeing process - Shamey, R.; Zhao, X. (Woodhead publishing in textiles ;, 2014)
With increased environmental awareness and rising costs, manufacturers are investing in real time monitoring and control of dyeing to increase its efficiency and quality. This book reviews ways of automating the dyeing process as well as ways of understanding key processes in dyeing, including dye transport in fluid systems. This understanding is then used to create models to simulate the dyeing process which can then be used to develop appropriate measurement and control systems. Control of variables such as temperature, pH, conductivity and dye concentration can then be used to ensure a more consistent and cost-effective dyeing process.